GRAMMATICAL HOMONYMY OF THE PARTICLES ON, OS’, OT, OTSE - Джочка, І. Ф. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article examines the grammatical homonymy of the particles os’, on, otse, ot (and their synonyms os’de, os’dechky, ono, on-on (on-on-on), onde, ondechky, oto). It elucidates the paradigmatic and syntagmatic factors, conditioning the affiliation of words under analysis to adverbs or particles. It researches synonymic and antonymic relations of deictic nominations, contextual surrounding, characterizes varieties of adverbial semantics.